Unveiling Maternal Mortality Challenges in a Resource Limited Setting, Ethiopia: A Systematic Literature Review (British Journal of Multidisciplinary and Advanced Studies, 2023)
By combining data from five carefully chosen studies completed between 2014 and 2023, this systematic review aims to assess maternal mortality rates, risk factors, and related variables in Ethiopia.A thorough search of electronic databases was done, including PubMed, Scopus, and Google Scholar. Utilizing predetermined criteria, eligible studies were found, which led to the inclusion of studies carried out in various Ethiopian regions. A thorough quality assessment was done to make sure the chosen studies were reliable. Maternal mortality rates, primary and secondary risk variables, and systemic, socioeconomic, and cultural factors influencing maternal mortalities were all extracted from the data from these studies.In Ethiopia, the research found large regional variations in maternal mortality rates, with obstructed labor, postpartum hemorrhage, and hypertensive disorders of pregnancy emerging as the main risk factors. Disparities in education, age, living in remote areas, and restricted access to antenatal care services were secondary concerns. Notably, limited antenatal care services, rural residence, young maternal age, and a lack of education were linked to increased maternal death rates.The ongoing problem of maternal mortality in Ethiopia is highlighted by this systematic review. Even though there have been gains, particularly in metropolitan areas, there are still significant regional differences. Increasing access to high-quality healthcare, especially in rural areas, boosting education, and increasing the use of antenatal care are just a few of the multidimensional initiatives needed to address maternal mortality. In order to minimize maternal mortality and ultimately move Ethiopia closer to achieving Sustainable Development Goal 3, comprehensive and targeted policies must be put in place.